New opportunities for designing effective small interfering RNAs - Valdés, James J; Miller, Andrew D (Scientific reports, 2019)
Small interfering RNAs (siRNAs) that silence genes of infectious diseases are potentially potent drugs. A continuing obstacle for siRNA-based drugs is how to improve their efficacy for adequate dosage. To overcome this obstacle, the interactions of antiviral siRNAs, tested in vivo, were computationally examined within the RNA-induced silencing complex (RISC). Thermodynamics data show that a persistent RISC cofactor is significantly more exothermic for effective antiviral siRNAs than their ineffective counterparts. Detailed inspection of viral RNA secondary structures reveals that effective antiviral siRNAs target hairpin or pseudoknot loops. These structures are critical for initial RISC interactions since they partially lack intramolecular complementary base pairing. Importing two temporary RISC cofactors from magnesium-rich hairpins and/or pseudoknots then kickstarts full RNA hybridization and hydrolysis. Current siRNA design guidelines are based on RNA primary sequence data. Herein, the thermodynamics of RISC cofactors and targeting magnesium-rich RNA secondary structures provide additional guidelines for improving siRNA design.
Keywords: Hydrolysis; metoda Monte Carlo; RNA virová; párování bází; Argonaute Proteins; Humans; hořčík; messenger RNA; simulace molekulového dockingu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; hydrolýza; komplex RISC; termodynamika; Base Pairing; Molecular Docking Simulation; krystalografie rentgenová; Crystallography, X-Ray; lidé; Drug Design; Monte Carlo Method; RNA, Small Interfering; Argonaut proteiny; RNA, Messenger; malá interferující RNA; Thermodynamics; guide RNA, Kinetoplastida; konformace nukleové kyseliny; racionální návrh léčiv; RNA Interference; RNA, Viral; Nucleic Acid Hybridization; Nucleic Acid Conformation; RNA, Guide, Kinetoplastida; hybridizace nukleových kyselin; RNA-Induced Silencing Complex; RNA interference; Magnesium